Post-chikungunya arthritis: a longitudinal study in a tertiary care hospital in Bangladesh - Sigma Hossain; Minhaj Rahim Choudhury; Md. Ariful Islam; Md. Masudul Hassan; Surayea Yeasmin; Farzana Hossain; Mohammad Mostafa Zaman (Tropical Medicine and Health, 2022)
Abstract Background and objective To identify the clinical patterns and consequences of post-chikungunya arthritis was the study's objective. Methods This longitudinal study was carried out among 143 Chikungunya virus (CHIKV) infected adult patients at the rheumatology department, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, during the outbreak of CHIKV infection in 2017. The disease was categorized into three phases: acute or febrile (lasting up to 10 days), subacute (11–90 days), and chronic (> 90 days). Patients who progressed towards the chronic phase were followed up to 1-year. Post-CHIKV de novo chronic inflammatory rheumatisms (CIRs) were characterized by persistent mono or oligoarthritis, undifferentiated polyarthritis, or meet the criteria rheumatoid arthritis (RA) or Spondyloarthritis (SpA). In addition, functional status was assessed by the validated Bangla version of the Health Assessment Questionnaire (HAQ). Results Mean age was 43.3 ± 11.5 years, and 51.0% were male. Within 1-year follow-up, 60 (41.9%) patients were suffering from arthralgia/ arthritis. Of them 52 patients did not have any pre-existing arthralgia/arthritis. 35 (65.3%) had undifferentiated arthritis, 10 (19.2%) had SpA, and 7 (13.5%) had RA. Patients with pre-existing rheumatological disorders, 6(4.2%) had SpA, 1(0.7%) had RA and 1(0.7%) had osteoarthritis. Polyarthralgia (n = 33, 55.0%) and polyarthritis (n = 20, 33.3%) were the main presentations. Female gender (OR: 0.45; CI: 0.21–0.96), positive IgG (OR: 0.30; CI: 0.12–0.76), and moderate to severe functional disability (OR: 3.46; CI: 1.62–7.40) were independent predictors of developing chronic post-CHIKV rheumatism. Conclusions At 1-year follow-up, more than one-third of the patients remained symptomatic. Female gender, positive IgG, and moderate to severe functional disability contributed to the development of chronicity.